Stacking in micellar electrokinetic chromatography for on-column sample pre-concentration of hydrophilic organophosphorus pesticides - Wan Aini Wan Ibrahim, author; S. M. Monjurul Alam, author; A. B. Sulaiman, author; Shigeru Terabe, author; International Symposium on Capillary Chromatography and Electrophoresis (ISCCE 2009) (33rd : 2009 : Oregon, USA) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL